Multiposition Rotation Interference Absolute Measurement Method for High-Precision Optical Component Surfaces. (15th September 2021) - Zhu, Xueliang; Nie, Fengming; Liu, Bingcai; Liu, Ruikun; Tian, Ailing
Abstract : Modern optical engineering requires increasingly sophisticated interferometry methods capable of conducting subnanometer scale measurements of the large aperture, high-precision optical component surfaces. However, the accuracy of interferometry measurement is limited to the accuracy with which the surface of the reference mirror employed in the interferometer system is known, and the influence of gravity-induced deformation cannot be ignored. This is addressed in the present work by proposing a three-flat testing method based on multiposition rotation interference absolute surface measurement technology that combines the basic theory of N -position rotation with the separability of surface wavefront functions into sums of even and odd functions. These functions provide the rotational symmetric components of the wavefront, which then enables the absolute surface to be reconstructed based on the N -position rotation measurements. In addition, we propose a mechanical clamping combined with computational method to compensate for the gravity-induced deformations of the flats in the multiposition rotation absolute measurements. The high precision of the proposed absolute surface measurement method is demonstrated via simulations. The results of laboratory experiments indicate that the combination compensation method provides the high-precision surface reconstruction outcomes. The present work provides an important contribution for supporting the interferometry measurement of large aperture, high-precision optical component surfaces.